The national economic empowerment development strategy (needs), libraries and persons with Special needs (2007)
The role of the library in the National Economic Empowerment Development Strategy (NEEDS) programme is identified and ways in which services are to be rendered to persons with disabilities, people in special circumstances, (e.g. orphans, refugees), people infected, with HIV/AIDS, poor persons, and exceptional children. These persons have economic, social, political, health and other needs which should be exclusively provided for in a civilized society, and their empowerment a major concern as many of them arc especially talented. National, Public, Special, University, School, NGO and Private Libraries’ efforts in special information provision to them is critically analyzed through a survey of fifteen libraries purposively selected, using observation and interview methods. Results showed that only about 42% of the libraries studied make provisions, 14% do not; while 35% make general provisions which may not always suit needs of ‘special’ clients. Challenges and prospects of libraries, information and resource centres in the empowering of persons with special needs through the NEEDS programme arc discussed. It is recommended that peoples’ value orientation change, basic infrastructure be put in place, and proper monitoring of NEEDS at the State and Local government levels be carried out, with libraries giving information and education support.